History, historians and development policy a necessary dialogue - Bayly, Christopher Alan 1945-2015; Rao, Vijayendra; Szreter, Simon 1957-; Woolcock, Michael 1964- (Manchester University Press, 2011)
Leading historians and policy advisors explore the implications of incorporating historical sensibilities into key development policy issues
Keywords: Policy sciences; History; Social sciences and history; Political science / Decision making; Historians; Economic development; Public health; Natural resources / Management; Geschichte; Politische Wissenschaft; Wirtschaftsentwicklung; Geschichtswissenschaft; Entwicklungspolitik; Aufsatzsammlung